KEPERCAYAAN DIRI PEDAGANG ASONGAN DI LINGKUNGAN FKIP UNIVERSITAS RIAU - Ayu Rezky Ramadhany; Desti Irja; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to find out how self-esteem among beach vendors in the circle of FKIP Riau University. This study uses a descriptive method with a qualitative approach. The research subjects in this study were 4 people: techniques for collecting data using interviews, observation and documentation. Data analysis techniques using Triangulation. The results of the research are how individuals trust the actions of beach vendors, namely the beach vendors are certain of the actions taken. Know the risks of decisions taken and influence the skills of beach vendors and improve the family economy. ownership of beach vendors and improvement of the family economy. While individuals are confident that they are accepted by beach vendors at other beach vendors because of the way the street vendors mix with other beach vendors. Moreover, they believe in themselves and already have the calm attitude of beach vendors in their abilities.Key Words: Trust, beach vendors